Bekennende Kirche und Bürgerrechtsbewegung: Resistenz vor dem Hintergrund großkirchlicher Bestandserhaltung, politischer Theologien und totalitärer Ideologien im NS- und SED-Staat - Besier, Gerhard (Kirchliche Zeitgeschichte, 1996)
No proof has been produced so far that those theologians and church lawyers who worked with the GDR's Ministry for State Security were in fact trying to overthrow the regime. Any possible correspondence or comparisons of their activities with those of the conspiratorial Resistance during the Nazi period, as in the case of Dietrich Bonhoeffer, should not therefore be taken for granted. In the "Third Reich" the Protestant churches, as is well known, were divided into rival camps. This was not the case in the GDR. The impetus for the separation and the resistance of the Confessing Church under the Nazis was drawn from theological insights, as expressed in the Barmen Declaration. The Confessing Church attacked heresies within the church, rather than opposing the Nazi state as such. But in the GDR, at least from the beginning of the 1970s, opposition groups drawn largely from the protestant milieu campaigned for changes in the social and political structures, such as the realisation of human rights. In pursuit of such goals they made use of the church's relative free room for action. Several clergymen participated in these groups, and indeed took leading roles. But as the conflict between these opposition groups and the Communist government became sharper, so the relationship between such church-based groups and the church leadership became more strained. Tensions between their respective objectives became more obvious, and finally led to a separation of these political "dissidents" from the church. In fact, after the overthrow of both regimes, it can now be seen that neither the efforts of the Confessing Church, nor the reformist campaigns of the opposition forces in the GDR, were to prevail against the entrenched positions of the church leadership or of the political parties. Their impulses for reform must therefore be regarded as no more than passing episodes.